Venomics and pharmacological activities of Malaysian kraits : bungarus candidus and bungarus fasciatus - Othman, Iekhsan; Ahmad Rusmili, Muhamad Rusdi (Idaman Pharma Sdn. Bhd., 2016)
Bungarus candidus (Malayan krait) and Bungarus fasciatus (Banded krait) are two medically important elapid species found in Southeast Asia countries. The reported cases of envenoming by Bungarus candidus and Bungarus fasciatus are limited with very limited data available. The venom of these species has been known to contain highly potent presynaptic (β- neurotoxins) and postsynaptic (α-neurotoxins) neurotoxins which prevent the acetylcholine release and receptor binding, respectively at the neuromuscular junction. The venom from both species contain complex mixture of a myriad of toxins that are yet to be discovered and characterized. Recent case reports and studies, have indicated that the activities of the venoms are not limited to neurotoxic activity only but could contribute to other lethal activity that affect other major organs. Furthermore, the venoms could have geographical variation as they are widely distributed throughout Southeast Asia. The variation in their venom will definitely affect the effectiveness of the available antivenom and the overall success in managing envenoming. This paper will highlight the works that have been conducted on the Malaysian Bungarus candidus and Bungarus fasciatus venom and toxins using isolated tissue preparation and proteomic techniques. The future direction of the Bungarus candidus and Bungarus fasciatus venom research, its importance in the management of krait envenoming and potential in bioprospecting for novel therapeutics and biomedical research tools will be discussed. In addition, the need for better and systematic krait bite case reporting will be emphasized. This study also explore the diversity of different molecules for bioprospecting, allowing more applied research to be conducted in the future.